Mini review of magnetic flux leakage detection technology for long-distance oil and gas pipelines - Wang Jie; Mohd. Kamal Mohd. Shah; Choong, Wai Heng; Nahiyan Al-Azad (Global Academic Excellence, 2024)
Long-distance oil and gas pipelines are a crucial means of energy transportation, and leaks in pipelines can lead to significant environmental and human losses. Therefore, it is necessary to adopt defect detection technology to regularly inspect pipelines, ultimately achieving the purpose of maintenance and repair of oil and gas pipelines. This paper introduces common types of defects in oil and gas pipelines, as well as commonly used defect detection methods. It focuses on the principle of magnetic flux leakage detection, analyzes factors affecting the results of magnetic flux leakage detection, and prospects the future development direction of magnetic flux leakage detection technology.